Factors Associated with Stunting in Adolescents in Integrated Health Post in Pariaman, Padang, West Sumatera, Indonesia - Putri, Azzahra Nadya; Retno Dewi, Yulia Lanti; Priyatama, Aditya Nanda (Journal of Maternal and Child Health, 2023)
Background: Stunting refers to irreversible physical growth retardation accompanied by cognitive decline that can last a lifetime and affect the next generation. This research was conducted to determine the factors that influence the incidence of stunting in adolescents at the Youth Posyandu Kota Pariaman. Subjects and Method: This was a cross sectional study. The population is all adolescents aged 10-18 years who are registered at the Kp. Jawa I with 52 people and Andestura Tungkal Selatan integrated health posts with 34 people. The sampling technique uses total sampling. Statistical test used chi square bivariate analysis. The dependent variable was stunting. The independent variables were gender, age, physical activity, and socioeconomic. Results: The results showed that gender (p=0.899), age (p=0.082), and physical activity (p=0.829) had no effect on the incidence of stunting in adolescents. Socioeconomic effect on the incidence of stunting in adolescents (p <0.001). Conclusion: There is no influence between gender, age, physical activity on the incidence of stunting because the nutritional status of stunting illustrates a disturbance in height growth that lasts for a long period of time so that it cannot be described by gender, age or physical activity. Socio-economic status that can affect the growth process includes income. Family income affects a person's ability to access certain foods which will affect the nutritional status of children. Someone with a low socioeconomic status has limited ability to access certain foods, so they are at risk of consuming less food. Keywords: gender age, physical activity, socioeconomic, stunting. Correspondence: Azzahra Nadya Putri. Masters Program of Human Nutrition, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta, Central Java 57126, Indonesia. Mobile: 082210112490. E-mail: azzahranadya09@student.uns.ac.id.